Kebijakan Dividen Memoderasi Pengaruh Kinerja Keuangan Terhadap Nilai Perusahaan (Studi Kasus Perusahaan Pertambangan Terdaftar Di Bursa Efek Indonesia Tahun 2016-2023 - Bayu Perkasa Ritzki Darmawan; I Made Suidarma (Yayasan Literasi Ilmiah Indonesia, 2024)
Purpose: This study aims to analyze the effect of liquidity, leverage, and profitability on firm value, with dividend policy serving as a moderating variable, in mining companies listed on the Indonesia Stock Exchange (IDX) during the 2016-2023 period. Method: The data used in this study consists of secondary data obtained from corporate financial reports available on the official website of the Indonesia Stock Exchange (IDX). The analysis methods employed include panel data regression and Moderated Regression Analysis (MRA). Finding: The study results indicate that liquidity, leverage, and profitability each have a significant effect on firm value. Additionally, dividend policy is proven to act as a moderating variable that strengthens the relationship between profitability and liquidity on firm value but weakens the effect of leverage. Novelty: This study contributes to the financial literature by highlighting dividend policy strategies and financial performance management as efforts to enhance firm value in the mining sector.